Antibacterial and Antifungal Activities of the Leaf Exudate of Aloe megalacantha Baker - Demoze Asmerom; Tesfay Haile Kalay; Gebrehiwot Gebremedhin Tafere (International Journal of Microbiology)
Infectious diseases caused by fungi and bacteria are among the major causes of illness and death worldwide. This is mainly implicated by the antimicrobial resistance of the current treatment regimens. Since plant products are house stores of bioactive compounds, it is essential to screen plant-based antimicrobials to come up with novel medicines that counter the grave consequences of antimicrobial resistance. In the folk medicine of Ethiopia, Aloe megalacantha is used for the treatment of wound, dandruff, malaria, diabetes, impotence, colon cleansing, amoeba, ascariasis, abdominal pain, urine retention, snake bite, and evil eye. Hence, the present study was aimed to evaluate the antibacterial and antifungal effects of the leaf exudate of Aloe megalacantha. Agar well diffusion was employed to determine the antibacterial and antifungal effects. Six bacterial strains, namely, S. aureus (standard), S. aureus (clinical isolate), E. coli ATCC 25922 (standard), E. coli (clinical isolate), K. pneumoniae (standard), and P. aeruginosa ATCC 27853 (standard), and four fungal strains such as C. albicans, C. glabrata, C. tropicalis, and C. krusei were studied. The leaf exudate showed the highest activity against C. krusei with an average zone diameter of 22.49 ± 0.47 mm at 400 mg/mL. Among the bacterial species, S. aureus ATCC 29213 (standard) was the most sensitive with an average zone of diameter of 16.63 ± 0.12 mm at 200 mg/mL. Thus, the present findings support the folklore use of Aloe megalacantha for the treatment of different microbial infections.